On Esterne day in þe dawing (Cambridge University Library, MS Dd. 1.1, ff. 30r—32v): Critical edition - Elisa Mastromatteo (Filologia Germanica)
The present work follows on from Pickering’s paper concerning a 268-line poem he calls Story of the Resurrection, which examines an error in The Index of Middle English Verse, where the text is considered one of the two copies of a reworking of the so-called Resurrectio Christi, part of the Southern Passion. It is in fact the only copy of a Resurrection poem, which Pickering attributes to a 14th-century South-East Midland dialect and he claims that it was probably composed in the early part of the century. The present paper intends to discuss Pickering’s work and presents a new critical edition of the anonymous and untitled poem which begins On Esterne day in þe dawing. Palaeographical evidence will confirm Pickering’s dating of the manuscript to the first half of the 15th century, while linguistic elements will point to the turn of the 14th century and, in line with the Linguistic Atlas of Late Mediaeval English, to the Isle of Ely, East Midlands, for the dialect in which the text was written. Stylistic features will reveal an original poet who cannot be identified with Richard Rolle of Hampole.